The Media Development PPKn Learning in The Form of an Android-Assisted Digital Pocket in Pancasila Material as Life Values for Students of State Primary School 106866 Cemara Tp.2023/2024. - Nurjanah, Bela (Berpusi Publishing, 2023)
This research was motivated by the lack of activeness of class IV students in PPKn learning because the learning media used was less interesting, resulting in a lack of active response from class IV students when learning was in progress. The aim of this research is to find out how to develop digital pocket book media in an effort to increase student learning activity and to find out the increase in the practicality of using digital pocket book learning media on the responses of students and teachers after using pocket book learning media for class IV students at SD. Negeri 106866 Cemara. With the development of smartphones, they should be put to good use, especially as learning media, which can improve the quality of education in Indonesia. The results of increasing student learning activity with the development of digital pocket book media have increased. This is known by the students' responses seen after using digital pocket book media compared to before using digital pocket book media. It is said that digital pocket book learning media can increase students' active learning at SD Negeri 106866 Cemara. The results of the practicality of digital pocket book learning media for teacher responses obtained a total score of 46 with a percentage of 83% with very practical criteria. Meanwhile, for student responses, a total score of 332 was obtained with a percentage of 88% with very practical criteria. So from the results of the practicality of the teacher and student responses above, it can be said that the assessment criteria are very practical as a learning medium for digital pocket books in class IV SD. Negeri 106866 Cemara.